Divorce implication on children: mitigation from Islamic perspectives - Karim, Fatimah (2024)
Divorce, while permissible in Islam, carries significant implications, particularly for children. The impact on their emotional, psychological, and social development can be profound. However, Islamic teachings provide guidance on how to mitigate these adverse effects, emphasizing the welfare of children and the responsibilities of both parents’ post-divorce. This article explores the implications of divorce on children and offers mitigation strategies from Islamic perspectives, supported by scholarly interpretations, Quranic verses, and Hadith.